2022
DOI: 10.1039/d2ce01215d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of halides and coordination mode of 4-amino-2,1,3-benzothiadiazole on the luminescence properties of its Zn complexes

Abstract: We report a systematic study of structure-luminescence relationship of novel coordination compounds [ZnL2Br2] (1), [ZnLBr2]n (2), [ZnL2I2] (3) and [ZnLI2]n (4) with 4-amino-2,1,3-benzothiadiazole (L). Variation of the halide and reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Zinc( ii ) and cadmium( ii ) complexes establish one of the most important classes of emissive compounds. 71–121 Earlier, we synthesized a series of mononuclear zinc( ii ) and cadmium( ii ) complexes with hybrid ligands containing a 2,2′-bipyridine moiety and natural terpene (+)-limonene or (+)-3-carene moieties and demonstrated that they exhibit luminescence with the quantum yield increasing in the following order: free ligand < cadmium( ii ) complex < zinc( ii ) complex. 122 The complexes with the limonene derivative demonstrate excitation wavelength–dependent emission with nanosecond and microsecond lifetimes of the excited states.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc( ii ) and cadmium( ii ) complexes establish one of the most important classes of emissive compounds. 71–121 Earlier, we synthesized a series of mononuclear zinc( ii ) and cadmium( ii ) complexes with hybrid ligands containing a 2,2′-bipyridine moiety and natural terpene (+)-limonene or (+)-3-carene moieties and demonstrated that they exhibit luminescence with the quantum yield increasing in the following order: free ligand < cadmium( ii ) complex < zinc( ii ) complex. 122 The complexes with the limonene derivative demonstrate excitation wavelength–dependent emission with nanosecond and microsecond lifetimes of the excited states.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by these encouraging examples, we study the luminescent properties of novel Au(I) complexes 1 , 2a , and 2b with two closely related ligands bearing benzothiadiazole (btd) moiety. In this context, amino-substituted btds open up a great scope for the design of photoactive materials: a slight variation of the composition and structure of btds results in a wide variation of energetic characteristics of electronic transitions, which is the key to fine-tuning the photophysical properties [ 24 , 25 , 26 , 27 ]. Herein, we chose two phosphorus-nitrogen ligands, comprising the NH-btd moiety as a chromophore, and PPh 2 moiety as a readily accessible unit for the metal coordination.…”
Section: Introductionmentioning
confidence: 99%